Cold-sensitive expression of transformation by a host range mutant of type 5 adenovirus. - Babiss, L E (1983)
hr1, an E1a (0-4.5 map units) host range mutant of type 5 adenovirus (Ad5), transformed a cloned rat embryo fibroblast (CREF) cell line at about a 5-fold higher frequency than wild-type (wt) Ad5 when cells were cultured at 37 degrees C. However, if the cells were infected with hr1 and maintained at 32 degrees C morphological transformation did not occur. When infected cells were shifted from 32 degrees C to 37 degrees C 2 wk postinfection, the frequency of transformation by 6 wk was identical to that of cells grown continuously at 37 degrees C, whereas cultures shifted from 37 degrees C to 32 degrees C 2 wk postinfection displayed a greater than 96% reduction in morphological transformation. hr1-transformed cells had a fibroblastic morphology as contrasted with the typical epithelioid morphology of wt Ad5-transformed cells, but hr1- and wt Ad5-transformed cells had similar saturation densities, growth rates, and agar cloning efficiencies when assayed at 37 degrees C. However, when cells transformed by hr1 at 37 degrees C were grown at 32 degrees C, they had a saturation density close to that of normal CREF cells and grew at a lower efficiency in agar than wt-transformed cells. DNA transfer/hybridization analysis of two hr1-transformed cloned cell lines, A2 and B3, indicated that A2 cells contained a complete integrated copy of the Ad5 genome, whereas in B3 cells only part of the Ad5 genome was integrated. RNA transfer and RNA/DNA filter hybridization analyses indicated that the types of viral messenger RNAs and the relative amounts of RNA transcribed were similar in the A2 and B3 cell lines when they were grown at 32 degrees C and 37 degrees C. Indirect immunofluorescence, with antisera from hamsters bearing Ad-induced tumors, indicated a temperature dependence in staining--i.e., cells grown at 37 degrees C or shifted from 32 degrees C to 37 degrees C contained intense, particulate staining in the nuclear region, whereas the staining was decreased significantly in cells cultured at 32 degrees C and in cells shifted from 37 degrees C to 32 degrees C. These findings indicate that the gene product affected by the hr1 mutation is cold sensitive and is essential for the expression of the characteristics that identify the transformed cell.